MODEL OF STRENGTHENING BRAND LOYALTY FOR EDC (Electronic Data Capture) USERS OF BANK RAKYAT INDONESIA (Persero) LTD. - Sandi Sutopo Ariwibowo; Widodo Widodo2 (UNISSULA, 2017)
The present study aimed to test a model in which service quality and social media marketing predict brand trust and brand loyalty. A total of 100 respondents completed questionnaires on service quality, social media marketing, brand trust and brand loyalty. Results from structural equation modeling based smartPLS 3.0 confirmed that 1) service quality was positively related to brand trust and brand loyalty; 2) brand trust was positively related to brand loyalty; and 3) social media marketing moderated the relationships between service quality and brand trust as well as service quality and brand loyalty.Keywords: Service quality, Social media marketing, Brand trust,Brand loyalty.